1990
DOI: 10.1002/ssu.2980060309
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory anesthesia

Abstract: Ambulatory surgical procedures are a large and increasing fraction of all surgery in the United States. A specialized health care team must be assembled to care for these patients and meet their special needs. Ambulatory surgery patients should be selected according to medical and psychosocial criteria. Patient preparation includes a history and physical examination, limited laboratory tests, empty stomach, and appropriate monitoring. Premedication should be supportive, and verbal as well as medicinal; drugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Discharge After Regional Anesthesia Patients undergoing regional anesthesia should expect the same standard of postoperative care as those who have undergone GA (29). It is acceptable to send a patient home with an anesthetized limb properly protected, with careful written and verbal instructions, and with a 24-h contact telephone number (35). For example, some authors have demonstrated significantly faster discharges after regional techniques (29).…”
Section: Is Voiding Necessary Before Discharge?mentioning
confidence: 99%
“…Discharge After Regional Anesthesia Patients undergoing regional anesthesia should expect the same standard of postoperative care as those who have undergone GA (29). It is acceptable to send a patient home with an anesthetized limb properly protected, with careful written and verbal instructions, and with a 24-h contact telephone number (35). For example, some authors have demonstrated significantly faster discharges after regional techniques (29).…”
Section: Is Voiding Necessary Before Discharge?mentioning
confidence: 99%
“…[24][25][26] DOX, one of the most effective chemotherapy drugs, was commonly used in the treatment of various cancers, such as breast cancer, lung cancer, ovarian cancer, etc. [27][28][29] However, the clinical dose of DOX is seriously limited due to its severe toxic side effects, especially for its cardiotoxicity. [30][31][32] To circumvent these limitations, numerous polymeric prodrugs with DOX conjugated through pH-cleavable hydrazone bonds have been fabricated.…”
Section: Introductionmentioning
confidence: 99%